SYSTEMATIC REVIEW (METASYNTHESIS) PENGARUH PJBL TERHADAP KEAKTIFAN SISWA - NR Siahaan, Fadillah; Fadilah, Muhyiatul (Jurnal Biogenerasi, 2026)
Student activity in the process of teaching and learning activities can be seen from the learning methods carried out. The aim of this research is to determine the effect of PJBL on student activity. The research method used in writing this literature review is systematic review meta synthesis, which is a qualitative technique used to combine similar primary data to obtain a new understanding of the problem at hand. This research aims to examine the results of previous studies, in order to determine the effect of PjBL on student activity. The data source used was taken from an online data bank with the keyword "Project Based Learning on student activity." The articles obtained were selected using specified criteria, and after screening 20 reference articles were obtained. The data banks used are Google Scholar, and Neliti. Based on a systematic meta synthesis review, it is clear that there is an influence between the PjBL learning model on student activity.